Heuristic Algorithms for Matching Geospatial Databases: Lexical and Semantic Analysis with Tree-Based Representations - Zaslavskyi, Volodymyr; Satanovskyi, Dmytro; Tsitskishvili, Givi (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
The paper explores heuristic approaches to matching geospatial databases, focusing on the Ukrainian context. Central methods include lexical and semantic analysis, hierarchical tree-based representations of geographic structures, and decision-making on graphs. The proposed framework emphasizes scalability and computational efficiency, providing a foundation for integrating more complex models in future research.